A computational study for axial rotation effects on heat transfer in rotating cans containing liquid water, semi-fluid food system and headspace - Erdogdu, Ferruh; Tutar, Mustafa (International journal of heat and mass transfer, 2012)
Thermal processing is the most significant part of the food industry, and common thermal processing, i.e. canning, is still the most effective way to preserve foods even though some innovative approaches for both thermal and non-thermal processing are emerging. Rotational processes are applied to liquid and semi-liquid canned products to increase heat transfer rate and reduce processing time and energy requirements. The major challenge in this process lies in the physical properties of the food product (density and viscosity) due to their effects on producing rotational and gravitational forces. Headspace also plays a significant role in agitation via the effect of rotation speed. Based on this, rotation speed and effects of physical properties are investigated extensively in this computational study applying a finite volume based volume of fluid method tracking algorithm. Evolution of temperature in a rotating two-phase fluid system consisting of a horizontal can with its liquid content (water and food material) and headspace (air) is determined with velocity field at rotation speeds from 0 to 160rpm. The corresponding rotational Reynolds number range from 1700 to 27,200 and 0.88 to 14.1 for water and food phases, respectively. Differences in the heat transfer rates of air–water and air–food material systems are attributed to the development of rotational forces (centrifugal buoyancy and Coriolis forces) compared to the gravitational buoyancy forces. The negative effect of increasing rotation speed on temperature increases over 10rpm depending upon the density variations of the food product will be useful in canning industry to improve rotary thermal processing and to optimize heating rates during rotation. This also signifies determining the optimal processing conditions with respect to the physical properties of the food product (density and viscosity) and rotation speed.